2011
DOI: 10.3855/jidc.1281
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus gallinarum meningitis: a case report and literature review

Abstract: We report a case of Enterococcus gallinarum meningitis in a 53-year-old female who was admitted to our hospital with a fever, headache, and consciousness disturbance one week after a life-saving craniotomy operation. There was obvious neck stiffness; lumber puncture was performed and cerebrospinal fluid parameters were consistent with bacterial meningitis. The patient was given ceftriaxone and vancomycin for bacterial meningitis. Cerebrospinal fluid culture yielded an isolate which was identified as Enterococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
(12 reference statements)
1
15
0
1
Order By: Relevance
“…Although the normal strains of Enterococcus spp. are sensitive to antibiotics such as ampicillin and vancomycin, some Enterococcus strains are resistant to antibiotics . Results in the current study showed that each of the four oat groups demonstrated significantly lower ( P < 0.05) cecal or colonic Enterococcus spp.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Although the normal strains of Enterococcus spp. are sensitive to antibiotics such as ampicillin and vancomycin, some Enterococcus strains are resistant to antibiotics . Results in the current study showed that each of the four oat groups demonstrated significantly lower ( P < 0.05) cecal or colonic Enterococcus spp.…”
Section: Resultsmentioning
confidence: 51%
“…Enterococcus spp. are pathogens that can cause important clinical infections, including urinary tract infections, bacteremia, bacterial endocarditis, diverticulitis and meningitis . Although the normal strains of Enterococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…[1,11,12] The fi rst case of VRE meningitis described here is a case of postoperative meningitis in a patient who underwent craniotomy for excision of an acoustic schwannoma and had a postoperative CSF leak. 30, No.…”
Section: Discussionmentioning
confidence: 99%
“…Like clostridial meningitis, enterococcal meningitis is uncommonly documented in the literature. Most instances have occurred after neurosurgery 26 or as a complication of bacteremia in severely debilitated patients with neutropenia and cancer. 27 Few, if any, cases of traumatic implantation of an enterococcal species have been documented.…”
Section: Discussionmentioning
confidence: 98%